2023
DOI: 10.3390/genes14040782
|View full text |Cite
|
Sign up to set email alerts
|

tsRNA Landscape and Potential Function Network in Subcutaneous and Visceral Pig Adipose Tissue

Abstract: Noncoding RNAs (ncRNAs) called tsRNAs (tRNA-derived short RNAs) have the ability to regulate gene expression. The information on tsRNAs in fat tissue is, however, limited. By sequencing, identifying, and analyzing tsRNAs using pigs as animal models, this research reports for the first time the characteristics of tsRNAs in subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT). A total of 474 tsRNAs, 20 and 21 of which were particularly expressed in VAT and SAT, respectively, were found in WAT. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…34 Zeng et al 35 indicated that the triglyceride-glucose index is positively correlated with the occurrence of GDM, while Grieger et al 36 identified triglyceride concentration as an independent risk factor for GDM. Wang et al 37 investigated the role of various tRFs and microRNAs in regulating fatty acid metabolism within mammalian subcutaneous and visceral adipose tissues, with a particular focus on stearoyl-CoA desaturase (SCD). Despite these insights, further research is required to fully understand how tsRNAs influence the development of GDM through their involvement in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…34 Zeng et al 35 indicated that the triglyceride-glucose index is positively correlated with the occurrence of GDM, while Grieger et al 36 identified triglyceride concentration as an independent risk factor for GDM. Wang et al 37 investigated the role of various tRFs and microRNAs in regulating fatty acid metabolism within mammalian subcutaneous and visceral adipose tissues, with a particular focus on stearoyl-CoA desaturase (SCD). Despite these insights, further research is required to fully understand how tsRNAs influence the development of GDM through their involvement in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…LLMs have demonstrated remarkable potential in creative design. However, a critical challenge lies in effectively incorporating design rationality and domain-specific knowledge [11,42,64]. Several methods have emerged to address the domain knowledge embedding challenge in LLMs.…”
Section: Large Language Model With Domain Knowledge Integrationmentioning
confidence: 99%